Value of implanting and reimplanting feedlot heifers - Laudert, S.; Kuhl, Gerry L.; Schalles, R. (Kansas State University. Agricultural Experiment Station, 2011)
Implanting incoming feedlot heifers with Ralgro® or Synovex-H® increased weight gain an average of 9.4%. Reimplanting half way through the 119 day feeding period did not improve gain significantly. There were no differences between Ralgro and Synovex-H when used as the initial or second implant.
Keywords: Beef; Implants; Reimplanting; Feedlot heifers